Factors Influencing the Use of Intermittent Bladder Catheterization by Individuals with Spina Bifida in Brazil and Germany. Issue 1 (26th October 2016) - Faleiros, Fabiana; Pelosi, Giovana; Warschausky, Seth; Tate, Denise; Käppler, Christoph; Thomas, Elisabeth
Abstract: Purpose: Intermittent catheterization (IC) often is essential for individuals with spina bifida/myelomeningocele (SBM) and neurogenic bladder. This study aimed to identify and analyze the factors that influence the use of IC. Design and Methods: Descriptive study with convenience sampling. Data were collected using printed (Brazil) and online (Germany) questionnaires, and analyzed using multivariate logistical regression and analysis of variance. The study included 100 Brazilian and 100 German patients, aged 0–55 years, with SBM who utilized IC. Findings: Intermittent catheterization was used by 188 of the 200 patients. Three variables were important for predicting who did or did not use IC: no discontinuation of IC, absence of technical difficulty, and daily frequency of IC. Conclusions and Clinical Relevance: Findings suggest that difficulties with IC use experienced by spina bifida patients and their family members that predicted full discontinuation tended to be personal variables, rather than demographic or medical characteristics.